Formation of protein corona on interaction of pepsin with chitin nanowhiskers in simulated gastric fluid. (30th July 2022) - Wang, Yihui; Zhou, Liyang; Sun, Yujing; Mu, Hongyan; Li, Xiaodan; Wang, Yanfei; Sun, Qingjie
Graphical abstract: Highlights: Chitin nanowhiskers formed a protein corona in simulated gastric fluid. The corona decreased the charge of chitin nanowhiskers from 22.4 to 12.9 mV. The interaction forces were mainly hydrogen bonds and van der Waals forces. The slight changes in pepsin structure did not affect its activity. Abstract: Protein corona (PC) usually changes the physicochemical properties of nanoparticles (NPs) and determines their ultimate fate in the physiological environment. As NPs are widely used in food, it is important to obtain a deep understanding of PC formation in the gastrointestinal fluid. Herein, we explored the adsorption of pepsin to chitin nanowhiskers (CNWs) and their interactions in simulated gastric fluid. Results suggest that the binding of pepsin reduced the surface potential of CNWs from 22.4 ± 0.15 to 12.9 ± 0.51 mV and caused their aggregation. CNWs quenched the fluorescence of pepsin and induced slightly changes in its secondary structure containing a reduction in the β-sheet content (∼ 3%) and an increase in the random coils (∼ 2%). The isothermal titration calorimetry (ITC) data suggested that the interaction forces between CNWs and pepsin were mainly hydrogen bonds and van der Waals forces.